Aggregation of egg white peptides (EWP) induced by proanthocyanidins: A promising fabrication strategy for EWP emulsion. (30th January 2023) - Wen, Hedi; Li, Zihao; Li, Yuchen; Hao, Yanrui; Du, Zhiyang; Liu, Xuanting; Shang, Xiaomin; Liu, Jingbo; Zhang, Ting
Graphical abstract: Highlights: Presence of PC induced the formation of EWP emulsion. Aggregation of PC-EWP-EWP involved two steps, which was confirmed by ITC. PC-EWP (1:4) reduced the surface tension (6%) and increased the contact angle (53%). Absorption of EWP and aggregates o O/W interface improved emulsion stability. Abstract: Egg-white peptides (EWP, <1 kDa) have been shown to possess various bioactive properties. However, poor emulsification of EWP limits its application in functional foods. In this study, EWP aggregation induced by proanthocyanidins (PC) contributed to the improvement of emulsion properties. The two-step binding process of PC-EWP-EWP was confirmed by isothermal titration calorimetry, fluorescence spectroscopy, surface hydrophobicity, and Fourier transform infrared spectroscopy. We found that first EWP combines with PC via hydrogen bonding and hydrophobic interactions. Next, more EWPs bind to the EWP in PC-EWP via hydrogen bonding, thereby forming PC-EWP-EWP aggregates. The aggregates (PC to EWP ratio of 1:4) reduced the surface tension (6 %) and improved the contact angle (53 %). The co-adsorption of EWP and aggregates at the O/W interface improved the contact angle, protein adsorption rate, and emulsion stability. This study establishes EWP aggregates induced by PC as an effective emulsifier, thereby expanding the application fields of EWP.